Answer:
The equation is
![y=-x+4](https://img.qammunity.org/2020/formulas/mathematics/high-school/g1ykt5l37vjldx8sefi0gt7kezvrwxcj1q.png)
Explanation:
We know that the line must pass through the point (2,2) so it must verify the equation ⇒
a) y = x - 4
b) y = x + 4
c) y = -x + 4
If we replace the point (2,2) in the equation a)
that it is absurd. Therefore the point (2,2) does not belong to the line a)
If we replace the point (2,2) in the equation b)
therefore the point (2,2) does not belong to the line b)
Finally,
therefore the point (2,2) belongs to the line
![y=-x+4](https://img.qammunity.org/2020/formulas/mathematics/high-school/g1ykt5l37vjldx8sefi0gt7kezvrwxcj1q.png)
given a line
![y=ax+b](https://img.qammunity.org/2020/formulas/mathematics/high-school/pqmc9ex2vfu8vytlvrx6kksbnmrule6iim.png)
Where ''a'' is the slope. If we want to obtain a line which is perpendicular to this, we need to multiply by -1 the slope and reverse it ⇒
is perpendicular to the line
![y=(-(1)/(a))x+b](https://img.qammunity.org/2020/formulas/mathematics/high-school/p4t71dulz55evh2ygxb1acfomdqu1bl4vu.png)
Now, given the line y = x the slope is ''1'' ⇒ Any line with a slope of ''-1'' will be perpendicular
The slope of the line c) y = -x +4 is -1 ⇒ y = -x +4 is perpendicular to y = x
The correct answer is
![y=-x+4](https://img.qammunity.org/2020/formulas/mathematics/high-school/g1ykt5l37vjldx8sefi0gt7kezvrwxcj1q.png)